A Cost-Effective Approach to the Risk Reduction of Cable Fault Triggered by Laying Repeaters of Fiber-Optic Submarine Cable Systems in Deep-Sea - Yukitoshi Ogasawara; Wataru Natsu (Journal of Marine Science and Engineering, 2021)
Long-distance submarine cable systems, such as the transoceanic system, generally consist of a series of cables and repeaters. Repeater units are spaced at regular intervals to boost the attenuated optical signal and presently contain optical amplifiers in a pressure vessel made of copper alloy. Since the repeater unit is more massive than the cable, it pulls the cable catenary locally toward the seabed. In the 1990s, several studies numerically simulated cable behavior in the water and showed that the seabed slack runs short, and the seabed cable tension increases just before the repeater reaches the seabed. Therefore, it has been pointed out that an unarmored cable with a polyethylene sheath can be easily damaged. However, no reports have been published regarding the actual situation of cable faults related to the laying of repeaters. This study quantitatively analyzes the mechanism of cable damage related to the laying of repeaters, based on experiments, simulations, maintenance records, and a comparative analysis between the simulation results and actual cable faults. Cost-effective methods to mitigate cable faults triggered by laying a repeater in the deep sea are also explored to ensure mechanical stability during the design lifetime.